FORMULATION AND EVALUATION OF NANO GEL AROMATHERAPY FROM SANDALWOOD ESSENTIAL OIL (Santalum album L.) AS ANTIDEPRESSANT - Swari Santi, Made Dwike; Rika Kumara, Ni Wayan; Ayu Antari, Desak Made (Jurnal Farmasi Kryonaut, 2025)
Cases of mental health disorders in Bali have increased in early 2024. Usada Bali is a traditional Balinese treatment that uses traditional medicinal plants, one of which is Sandalwood (Santalum album L.) which can be used as an antidepressant. Topical preparations in the form of aromatherapy nano gel are suitable for use as antidepressant therapy because the consistency of the gel has a fairly high adhesive power so that the contact time on the skin is relatively longer than other preparations. This study aimed to determine the formulation and evaluation of sandalwood essential oil aromatherapy nano gel useful as an antidepressant. Method research observational experiment, observations were made on the organoleptic, homogeneity, pH of the preparation, and evaluation antidepressant. Statistical analysis was also carried out on the immobility time (Mus musculus) with the Anova test. Results of the study is formulations aromatherapy nano gel preparations of essential oils were in accordance. In this study, sandalwood essential oil positively contains triterpenoid compounds that have antidepressant activity. The aromatherapy nano gel preparations of sandalwood essential oil that there was a difference between the test group and the negative group and there is no difference between the test group and the positive group.